Implementasi Pelaksanaan Ketentuan Pasal 35 UU No.46 Tahun 2009 Tentang Pengadilan Tindak Pidana Korupsi Bertentangan Dengan Harapan Asas Peradilan Cepat, Sederhana Dan Biaya Ringan Terhadap Peradilan Tindak Pidana Korupsi Di Tingkat Kabupaten/Kota - Handrawan, Handrawan; Hasjad, Hasjad; Ustien, Dewi Oktoviana; Arpin, Syaiful (Jurnal Ilmiah Dikdaya, 2022)
Abstract :The focus of the study in this research is the implementation of the provisions of Article 35 of Law No. 46 of 2009 concerning Corruption Courts Contrary to the Expectations of Fast, Simple and Low Cost Judicial Principles for Corruption Courts at the Regency/City Level. This study aims to examine and analyze the subject matter, namely analyzing the problems of implementing the provisions of Article 35 of Law Number 46 Year 2009 concerning the court of corruption at the district/city level. To analyze the policy concept so that the judicial process for corruption at the district/city level can reflect the expectations of the principles of simple, fast and low-cost justice. To discuss these problems, the type of research used by the author is that this research is structured as "normative" research, namely research that is used to examine various positive legal provisions and general legal principles, in order to obtain scientific truth on the discussion of legal issues being studied. . Based on the results of the research, the implementation of the establishment of the criminal justice system for corruption in each district was not in accordance with what was expected. This means that what is expected with the reality that occurs does not match. Because until now the implementation of article 52 paragraph (2) has not materialized. The impact is that there are difficulties in the process of handling cases that must be resolved by the Corruption Crime Court and the increasing number and accumulation of cases, in addition to the long distance constraints from the corruption courts, a small budget, an average staff of only 2 public prosecutors. so that the settlement of corruption cases that are carried out becomes slow, this is certainly not in accordance with the principles of fast, simple and low-cost justice.